Identification of New Splice Sites Used for Generation of rev Transcripts in Human Immunodeficiency Virus Type 1 Subtype C Primary Isolates - Delgado, Elena; Carrera, Cristina; Nebreda, Paloma; Fernández-García, Aurora; Pinilla, Milagros; García, Valentina; Pérez-Álvarez, Lucía; Thomson, Michael M. (PLOS ONE, 2012)
The HIV-1 primary transcript undergoes a complex splicing process by which more than 40 different spliced RNAs are generated. One of the factors contributing to HIV-1 splicing complexity is the multiplicity of 3′ splice sites (3'ss) used for generation of rev RNAs, with two 3'ss, A4a and A4b, being most commonly used, a third site, A4c, used less frequently, and two additional sites, A4d and A4e, reported in only two and one isolates, respectively. HIV-1 splicing has been analyzed mostly in subtype B isolates, and data on other group M clades are lacking. Here we examine splice site usage in three primary isolates of subtype C, the most prevalent clade in the HIV-1 pandemic, by using an in vitro infection assay of peripheral blood mononuclear cells. Viral spliced RNAs were identified by RT-PCR amplification using a fluorescently-labeled primer and software analyses and by cloning and sequencing the amplified products. The results revealed that splice site usage for generation of rev transcripts in subtype C differs from that reported for subtype B, with most rev RNAs using two previously unreported 3'ss, one located 7 nucleotides upstream of 3'ss A4a, designated A4f, preferentially used by two isolates, and another located 14 nucleotides upstream of 3'ss A4c, designated A4g, preferentially used by the third isolate. A new 5′ splice site, designated D2a, was also identified in one virus. Usage of the newly identified splice sites is consistent with sequence features commonly found in subtype C viruses. These results show that splice site usage may differ between HIV-1 subtypes.